DETERMINANTS AND CHALLENGES OF CASSAVA PRODUCTION IN MANYU DIVISION, CAMEROON - Arrey, T.M.; Mbu, D. T.; Shillie, P.N. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analysed the determinants and challenges faced by cassava famers in Manyu, Cameroon. Primary data for the study was obtained from 400 cassava farmers with the use of a well-structured questionnaire. Data analysis shows that cassava production was dominated by females (95.5 %) in the study area and mean age (38.5). The probit results, revealed that marital status, social network, had training in cassava production, land tenure system, farmers’ monthly revenue from cassava products, and experience in cassava production influence cassava production in Manyu division, at 10%, 10%, 5%, 1%, 1% and 10% level of significance respectfully. While the major challenges faced by cassava farmers were; absent of quality cassava cuttings (91.25%), lack of agrochemicals (51.25%), high cost of labour (78%), credit facilities (72.75%), high cost of farm inputs (64%), absent of extension services (64.25) and pests and diseases (63.25%) where the sum of percentage of strongly agree and agree is greater that the percentage sum of disagree and strongly disagree. Formulation of policies to attract investment in cassava production such a tax exemption for private agricultural enterprises, easy access to land, increase the number of extension workers, training of farmers in cassava production and monitoring of cassava farms. The study recommended that projects in the cassava farming should target female and youths in large scale production and mechanisation.